ضوابط التفسير المنقول عن الصحابة - ابن عبد الرحمان, أحمد (University of Eloued جامعة الوادي, 2017)
القرآن الكريم كتاب هداية وعقيدة وإيمان، وكتاب فقه ودعوة، هو دستور ومنهج حياة، هو نور وضياء وشفاء، هو رسالة الله للناس كافة. عكف العلماء على تفسيره وبيان مراد الله منه منذ الزمن الأول، ولكن اختلفت في ذلك مناهجهم واتجاهاتهم، فمنهم من اعتمد الرواية والنقل، ومنهم سلك طريق الدراية والعقل، ومنهم من جمع بين الطريقين؛ فكان بين هذه المناهج بون كبير، واختلاف خطير. مما دفع بعض أئمة العلم، ممن تملكتهم الغيرة على الحق، والانتصار لكتاب الله، ليضعوا ضوابط وأصول وقواعد؛ تكون هي المرجع والأساس لكل من أراد تفسير القرآن، وميزان تتميز به تفاسير أهل الزيغ والتقصير، عن تفاسير أهل الحق والتبصير؛ فظهرت مؤلفات عدة تعنى ببيان هذه القواعد والأصول، ويأتي التفسير بالمأثور في صدارة هذه القواعد. واختلف في تفسير الصحابي؛ فرأى بعض أهل العلم أنه من قبيل التفسير بالمأثور مطلقا، ورأى آخرون غير ذلك. ووضع المحققون من علماء الأمة ضوابط لقبول ما ثبت عن الصحابة في التفسير؛ حتى يدخل ضمن مفهوم التفسير بالمأثور، ويسري عليه حكمه؛ ويتميز ما يلزم الأخذ به مما روي عن الصحابة ــ الكرام ــ عن ما لا يلزم . Abstract: Koran is a book of guidance, creed, and faith. It is a book of Fiqh and da'wa. It is constitution and way of life. It is the message of God to all people. Scholars has embarked on the interpretation of the Koran since the first time, But they differed in the approaches to this, some of them depended on narration, while others follow the path of reason and know-how, as others have depended on a combination of the two approaches. As a result, it was between these approaches a big difference. Thus pushing some scholars to put controls, principles and rules in order to be the reference and the basis for everyone who wants to interpret the Koran. Mathur interpretation comes in the forefront of these rules and controls. Differences regarding the interpretation of Alsahabi has happened, some scholars saw that it was such absolutely Mathur interpretation, some of them said otherwise in. Scholars put the controls to accept what is proven from the Sahabah of interpretation; in order to be entered within the concept of Mathur interpretation.
Controls of interpretation Transfused from the Sahabah
مجلة البحوث والدراسات المجلد 14 العدد 01 جامعة الوادي
Keywords: الصحابي، تفسير، ضوابط، المأثور; Alsahabi, interpretation, controls, Mathur